(untitled) (Ustozlar uchun, 2024)
In modern economic conditions, the financial resources of enterprises play an important role, since they create the conditions for a continuous production process, its stable growth, and also determine the competitiveness of an enterprise in the market. In the conditions of the formation and development of market relations, there is a lack of financial resources for many business entities. The lack of financial resources negatively affects the economic activity of enterprises, leads to the emergence and growth of debts to business entities, for wages and taxes. Therefore, the issue of forming a sufficient amount of financial resources of the enterprise for the implementation of economic activities becomes relevant. The totality of financial resources formed at the enterprise level determines the possibilities: increasing working capital, making the necessary capital investments, fulfilling financial obligations, meeting social needs, etc.